WASTE MANAGEMENT AND THEIR CONDITION ON THE AREA OF RAVA-RUSKA TERRITORIAL COMMUNITY IN LVIV REGION - Panas, Н.; Lysak, Г.; Firsanov, М.-Д.; Onyskovets, М.; Lopotych, Н. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
The article makes assessment of the state of waste management in Rava-Ruska territorial community. A particular attention is focused on the primary decisions made by managers of the territorial community during the war on the practical vision concerning the problems of waste management, the amount of which increased due to the presence of migrants, refugees, persons crossing the border. The scales and tendencies of solid waste production on the territory of Rava-Ruska territorial community in Lviv region are analyzed. The authors of the research clarified ntheir composition and properties for further ecologically safe handling. The experience of the methods and ways of dealing with solid household waste on the area of Rava-Ruska territorial community, in particular collection, transportation, burial, is consolidated. The existing processes of formation, collection, transportation, utilization and disposal of solid household. wastes on the area of Rava-Ruska territorial community in Lviv region have been studied. The subject of the research was the theoretical basis for improvement of the interdependent relations, which appeara in the process of formation, collection, transportation, utilization and disposal of solid household waste at the local level. The issue of eliminating gaps in legislation in the field of wartime waste was raised. A practical vision of the solutions of waste management is presented. Conceptual approaches to the implementation of an environmentally friendly model of waste management within the TC have been developed and stages of implementation of the "Roadmap for waste management in Rava-Ruska territorial community of Lviv region" have been proposed with consideration of the territorial features in the context of regional environmental security.